The evolving role of nurses in extracorporeal membrane oxygenation therapy - Hakami, Emad Ahmed; Alsomali, Ahlam Hassan; Alharbi, Mashael Eid (International Journal of Research in Medical Sciences, 2025)
Nurses managing extracorporeal membrane oxygenation (ECMO) have shifted from operating under a perfusionist-led framework to assuming full responsibility for ECMO care. This transition reflects a growing demand for sustainable, team-based ECMO delivery models. To review the evolving role of nurses in ECMO therapy, with emphasis on clinical responsibilities, education, training and leadership, this narrative review synthesizes findings from original studies and program evaluations describing nurse-led ECMO models, nursing competencies and educational initiatives. Nurses now monitor circuits, adjust settings, manage anticoagulation and lead emergency responses. Structured training programs, simulation exercises and competency validation have facilitated this role expansion. Studies report improved ECMO capacity, patient safety and program efficiency. Nurse-led ECMO models enhance resource use, team integration and care quality. Investment in training and interprofessional collaboration is vital for sustaining and expanding nursing roles in ECMO programs.